Association of Brucella Meningoencephalitis with Cerebrospinal Fluid Shunt in A Child: A Case Report - ABDINIA, Babak; BARZEGAR, Mohammad; MALAKI, Majid; BEHBOD, Haleh; OSKOUI, Shahram (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Abdinia B, Barzegar M, Maleki M, Behbod H, Oskoui Sh. Association of Brucella Meningoencephalitis with Cerebrospinal Fluid Shunt in a Child: a Case Report. Iran J Child Neurol. 2013 Winter:7(1):35-38. Brucellosis is an endemic zoonosis in Iran. It is a systemic infection that can involve any organs or systems of the body and have variable presentations. Ventriculoperitoneal (VP) shunt infections due to brucellosis have been rarely reported in the literatures. This is the history of a four years old boy who developed Brucella meningoencephalitis at the age of 42 months, whilst he had a VP shunt in situ for hydrocephalus treatment. Also, he presented brucellosis as acute abdomen. This patient was treated with trimethoprim-sulfamethoxazole, gentamicin and rifampicin. The shunt was extracted and all clinical and laboratory test abnormalities subsided through this management. We propose that in a patient with Brucella meningoencephalitis, the cerebrospinal fluid shunt system can be extracted and treatment with appropriate combination of antibiotics could be successful. Moreover, it shows that brucellosis should be considered in the differential diagnosis for acute abdomen and ascites in endemic regions. References 1. Hasanjani Roushan MR, Mohrez M, Samilnejad Gangi SM, Soleimani Amiri MJ, Hajiahmadi M. Epidemiological features and clinical manifestations in 469 adult patients with brucellosis in babol, Northern Iran. Epidemiol infect 2004;132(6):1109-14 2. Bouza E, García de la Torre M, Parras F, Guerrero A, Rodríguez-Créixems M, Gobernado J. Brucellar meningitis. Brucellar meningitis. Rev Infect Dis 1987; 9(4):810-22. 3. Young EJ. Brucella species. In: Mandell GL, Bennett JE, Dolin R, eds. Mandell, Douglas and Bennetts Õs Principles and Practice of Infectious Diseases. 5th ed. New York: Churchill Livingstone; 2000. p. 86-93. 4. Feiz J, Sabbaghian H, Miralai M. Brucellosis due to Brucella melitensis in children. Clinical and epidemiological observations on 95 patients studied in Central Iran. Clin Pediatr 1978;17:904-7. 5. Young EJ. Human brucellosis. Rev Infect Dis 1983; 5(5):821-42. 6. Llorens-Terol J, Busquets RM. Brucellosis treated with rifampicin. Arch Dis Child 1980;55(6):486-8. 7. FeizJ, Sabbaghian H, Miralai M. Brucellosis due to Brucella melitensis in children. Clinical and epidemiological observations on 95 patients studied in Central Iran. Clin Pediatr 1978;17:904-7. 8. Wald SL, McLaurin RL. Cerebrospinal fluid antibiotic levels during treatment of shunt infections. J Neurosurg 1980;52(1):41-6.